THE USE OF CLOZE PROCEDURE TO IMPROVE STUDENTS’ READING COMPREHENSION - Diah Ayu Primawati (English Education Department Slamet Riyadi University Surakarta, 2020)
Thisiresearch wassconducted innorder to improveestudents’ readinggcomprehension throughicloze procedureeat the VIII-A gradeestudents of SMP Negeri 1 Matesih. Theesubject of thissresearch consistssof 32 students. It wassa Classroom Action Research. Theeresearch tookktwo cycles. Eachhcycle consistssof planning, implementing,gobserving, and reflecting. Theiresearcher usediinterview, test, and documentiin collectingithe data. The dataaof the researchhwas analyzeddthrough qualitativeemethod for interviewaand document. Theeresearcher useddquantitative usingtt-test to measureewhether there wasssignificant improvementtbetween pre-testaand post-test 1 score,aand also post-test 1 and post-test 2 score. Besides, theeimprovement of students’sreading comprehensionncan be seennfrom the studentssreading achievement. Theeresult of meannscore for pre-testewas (51,5), post-test 1 (64,9), and post-test 2 (81,4). Then,tthe t-test valueeof cycleione was 13,4863 and the t-test value of cycleetwo was 17,1339. Baseddon the explanationnabove, it can beeconcluded that Cloze Procedureeis an appropriateestrategy to improveestudents’ readinggcomprehension. Key words: Cloze Procedure, Reading Comprehension, Classroom Action Research.